Graphene-loaded nickel−vanadium bimetal oxides as hydrogen pumps to boost solid-state hydrogen storage kinetic performance of magnesium hydride - Gao, Dong-qiang (2024)
To modify the thermodynamics and kinetic performance of magnesium hydride (MgH2) for solid-state hydrogen storage, Ni3V2O8-rGO (rGO represents reduced graphene oxide) and Ni3V2O8 nanocomposites were prepared by hydrothermal and subsequent heat treatment. The beginning hydrogen desorption temperature of 7 wt.% Ni3V2O8-rGO modified MgH2 was reduced to 208 °C, while the additive-free MgH2 and 7 wt.% Ni3V2O8 doped MgH2 appeared to discharge hydrogen at 340 and 226 °C, respectively. A charging capacity of about 4.7 wt.% H2 for MgH2 + 7 wt.% Ni3V2O8-rGO was achieved at 125 °C in 10 min, while the dehydrogenated MgH2 took 60 min to absorb only 4.6 wt.% H2 at 215 °C. The microstructure analysis confirmed that the in-situ generated Mg2Ni/Mg2NiH4 and metallic V contributed significantly to the enhanced performance of MgH2. In addition, the presence of rGO in the MgH2 + 7 wt.% Ni3V2O8-rGO composite reduced particle aggregation tendency of Mg/MgH2, leading to improving the cyclic stability of MgH2 during 20 cycles.